1-2a-a=-2(-2a+8)-2(a-6)

Simple and best practice solution for 1-2a-a=-2(-2a+8)-2(a-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1-2a-a=-2(-2a+8)-2(a-6) equation:


Simplifying
1 + -2a + -1a = -2(-2a + 8) + -2(a + -6)

Combine like terms: -2a + -1a = -3a
1 + -3a = -2(-2a + 8) + -2(a + -6)

Reorder the terms:
1 + -3a = -2(8 + -2a) + -2(a + -6)
1 + -3a = (8 * -2 + -2a * -2) + -2(a + -6)
1 + -3a = (-16 + 4a) + -2(a + -6)

Reorder the terms:
1 + -3a = -16 + 4a + -2(-6 + a)
1 + -3a = -16 + 4a + (-6 * -2 + a * -2)
1 + -3a = -16 + 4a + (12 + -2a)

Reorder the terms:
1 + -3a = -16 + 12 + 4a + -2a

Combine like terms: -16 + 12 = -4
1 + -3a = -4 + 4a + -2a

Combine like terms: 4a + -2a = 2a
1 + -3a = -4 + 2a

Solving
1 + -3a = -4 + 2a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-2a' to each side of the equation.
1 + -3a + -2a = -4 + 2a + -2a

Combine like terms: -3a + -2a = -5a
1 + -5a = -4 + 2a + -2a

Combine like terms: 2a + -2a = 0
1 + -5a = -4 + 0
1 + -5a = -4

Add '-1' to each side of the equation.
1 + -1 + -5a = -4 + -1

Combine like terms: 1 + -1 = 0
0 + -5a = -4 + -1
-5a = -4 + -1

Combine like terms: -4 + -1 = -5
-5a = -5

Divide each side by '-5'.
a = 1

Simplifying
a = 1

See similar equations:

| -3(5-2x)=-13(4x+1)-8x | | -x+5y=2 | | V^2+12+35= | | 13(5-2x)=-13(4x+1)-8x | | 9y+3y+48=180 | | 9x+3=2x+15 | | 7-2n=n-24 | | 3/5(10x-15)=27 | | 5-3(2x-7)=4(x+5)-6 | | -12+4(-3-x)=32-49 | | (5x+3y)(5x-3y)= | | 1.666d+.666=.25(d-2) | | 8x+3.1=-6+14.3 | | 1.666d+666=.25(d-2) | | 43+x=7 | | 14+2(y+3000)=1340 | | -49=6x-13-4c | | d+32=1400 | | -0.8=.13x-.21x | | 30+3y-7=10y-12-2y | | 4x+2+2x=4x+4x | | f-11=987 | | 1.666+.666=.25(d-2) | | x+6x=46207 | | 2x+y+10x-4y=180 | | 99x=3 | | 0=4x^3-6x^2+1 | | by+2=c | | 36-4=-13 | | -3(4m+3)-5=-30-8m | | y^2-6x+27=0 | | x+19+3x=-5-3x-11 |

Equations solver categories